Development of E-Sciebooklet on Environmental Issues Material to Foster Creative Thinking Skills of Junior High School Students - Sulistyaningrum, Anggie; Biru, Lulu Tunjung; Aprelia Resti, Vica Dia (Universitas PGRI Sumatera Barat, 2024)
The curriculum merdeka emphasize the ability to think creatively in the profile of Pancasila students. However, science learning in junior high school is still not optimal in fostering this creative thinking ability. One solution is the provision of e-sciebooklet teaching materials. This study aims to describe the level of product validity and analyze students' responses to e-sciebooklets on environmental issues to foster students' creative thinking skills. The research method used is Research and Development (R&D) with a 4-D model consisting of four stages, namely define, design, develop, disseminate. However, this research is limited to the development stage, which is the limited trial stage. The research instruments included validation sheets and student response questionnaires. The validity of the product was measured through a questionnaire assessed by 3 material expert lecturers, 3 teaching material expert lecturers, and 3 junior high school science teachers. Data acquisition was analyzed quantitatively and qualitatively. The results of the study show that the e-sciebooklet obtained an overall score from experts of 91.66% with the category of